حكمة مشروعية العدد والعدة في الطلاق - معابدة، زينب زكريا علي (الجامعة الأردنية - عمادة البحث العلمي, 2018)
This research paper will address some of the rulings related to divorce that Islamic Shari'a has established to end marital relationships. This, when all the doors to reconciliation have been shut. Also, when the negative aspects of staying together outweigh the positive ones. Finally, it will make the importance of the rulings apparent in achieving the objectives that will return the family involved with benefit and favor. The results of the research has shown that the legislation of the 'number' of times a divorce can be uttered makes it a long and complicated process which can affect all facets of life. Therefore, it requires patients to achieve the final desired outcomes of the divorce. In addition, the excessive nature of divorce-utterances is in fact a defamation of Shari'a objectives. It is therefore that Islamic Shari'a has placed a limit on divorce utterances at 3. As long as the Shari'a objectives were not met, then a burst of divorce utterances wouldn't be an apparent divorce case, but rather one utterance.
يتناول هذا البحث دراسة بعض أحكام الطلاق التي نظمتها الشريعة الإسلامية؛ لأنها العلاقة الزوجية التي سدت أبواب إصلاحها، وغلبت مفاسد إقامتها على مفاسد إبقائها. ويكشف عن أهمية هذه الأحكام في تحقيق حكم ومقاصد، تعود على الأسرة بالنفع والفائدة. ويقوم هذا البحث على المنهج التحليلي، حيث تم جمع المادة العلمية المتعلقة بمضمون البحث، ومن ثم تحليلها للخروج بالنتائج المطلوبة. ومما تقرر في النتائج: إن مشروعية العدد والعدة في الطلاق تجعله قرارا يمر في عملية معقدة طويلة النفس، تحتاج إلى دراسة وتقليب؛ لما ستكون عليه الحياة في كافة مجالاتها، وتستلزم الصبر للتأكد من الحاجة الحقيقية للطلاق. إن تجاوز العدد المحدد في الطلاق فيه افتئات على المقصد الشرعي؛ الذي من أجله حدد الشارع الحكيم الطلاق بثلاث طلقات، تتم على ثلاث مرات، وما دام أن مقصد الشارع لم يتحقق فالتلفظ بالطلاق دفعة واحدة لا يعد طلاقا باتا؛ بل يعد طلقة واحدة.
Keywords: الشريعة الإسلامية -- الفقه الإسلامي -- أحكام الطلاق -- عدة الطلاق